Stomach contents of birds from the Brazilian Cerrado savannas - Oniki-Willis, Yoshika; Willis, Edwin O. [UNESP]; Machado, Vera Ligia Letizio [UNESP]; Lopes, Leonardo Esteves (Springer Nature, 2022)
Birds are important bioindicators and have been frequently used to ascertain and monitor environmental changes. Therefore, even today in the twenty-first century, it is of great importance to study and accumulate basic information on birds’ natural history, including their diet. Here, we analyzed 180 stomach contents for 93 species of birds belonging to 34 families. These birds have been collected mostly in the Brazilian Cerrado savannas, with some few samples obtained in the Atlantic Forest. We found in the stomach contents analyzed mostly arthropods, especially the insect orders Coleoptera and Hymenoptera. Vegetable matter, especially fruits, grains, and unidentified seeds, was also prevalent, but it was often not possible to identify the botanical material, which was frequently ground up. This is one of the most comprehensive studies to date about the diet of Brazilian birds, covering a poorly sampled region in the state of Mato Grosso as well as understudied species.
Keywords: Birds; Cerrado; Diet; Neotropics; Stomach content analysis